Elective cesarean section without urethral catheterization - Senanayake, H (The Sri Lanka College of Obstetricians and Gynaecologists, 2005)
AIM: To determine the feasibility and safety of carrying out elective lower-segment cesarean section without urethral catheterization. METHODS: A prospective comparative study was carried out at a private hospital in Colombo, Sri Lanka. A pilot study involving 50 women was carried out to measure the volume of urine obtained at the beginning and at the end of cesarean section, using an indwelling catheter. In the main study, surgery was carried out without urethral catheterization on 344 women who had voided within the previous hour. RESULTS: The mean volume of urine collected at the beginning and at the end of surgery was 25.5 and 42.8 mL, respectively. This volume was calculated to be accommodated in spheres of 4.0 and 4.6 cm in diameter, respectively. In the main study, 73% had the bladder distended to a level <3 cm from the lower cut edge of the rectus sheath. In the remaining 27% it was above this level, but covered completely by Doyen's retractor. There were no cases of accidental cystotomy. The difference in the mean time taken for surgery in the two groups was not significant (P=0.30). Distress catheterization was required in two (0.58%). The rest voided after a mean of 8.76 h (SD=2.37). The majority (68.2%) voided in the toilet. The difference in the urinary infection rates between the two groups (6%vs 0.58%) was statistically significant (P <0.05). CONCLUSIONS: Cesarean section without urethral catheterization does not compromise the safety or ease of surgery. It reduces the risk of urinary infection.